2013
DOI: 10.3389/fnhum.2013.00237
|View full text |Cite
|
Sign up to set email alerts
|

The neural control of singing

Abstract: Singing provides a unique opportunity to examine music performance—the musical instrument is contained wholly within the body, thus eliminating the need for creating artificial instruments or tasks in neuroimaging experiments. Here, more than two decades of voice and singing research will be reviewed to give an overview of the sensory-motor control of the singing voice, starting from the vocal tract and leading up to the brain regions involved in singing. Additionally, to demonstrate how sensory feedback is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 138 publications
(209 reference statements)
9
97
0
2
Order By: Relevance
“…Dorsal stream involvement has been shown 571 previously for goal-related actions (Kravitz et al, 2011), speech production (Hickok & Poeppel, 2007) and 572 singing (Loui, 2015;Zarate, 2013) and is compatible with our fronto-parietal network observed in pianists 573 during musical action imitation. Moreover, since the audio contrast comprised frontal activation extending 574 to dorsal IFG, it is plausible that also during listening (although without imitation) a dorsal stream of 575 auditory information might have been involved for mapping sound to action simulated by pianists (Zatorre 576 et al, 2007).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Dorsal stream involvement has been shown 571 previously for goal-related actions (Kravitz et al, 2011), speech production (Hickok & Poeppel, 2007) and 572 singing (Loui, 2015;Zarate, 2013) and is compatible with our fronto-parietal network observed in pianists 573 during musical action imitation. Moreover, since the audio contrast comprised frontal activation extending 574 to dorsal IFG, it is plausible that also during listening (although without imitation) a dorsal stream of 575 auditory information might have been involved for mapping sound to action simulated by pianists (Zatorre 576 et al, 2007).…”
supporting
confidence: 80%
“…Ventral IFG, in turn, is known as endpoint of the auditory ventral stream that, in concert with 582 posterior temporal areas, is classically thought to process pitch information during singing (Berkowska 583 and Dalla Bella, 2009;Zarate, 2013) and to map sound to meaning (Hickok and Poeppel, 2007; 584 Rauschecker and Scott, 2009), compatible with our fronto-temporal network observed during listening.…”
supporting
confidence: 54%
“…Similar results were reported in singing, another sophisticated orofacial and laryngeal function in humans (for review see [4]): the vSI is activated bilaterally in a simple singing condition where subjects were asked to produce bisyllabic words melodically intoned at a certain pitch, and even during humming [5]. Moreover, several lines of evidence suggest that trained singers may rely more on somatosensory feedback than auditory feedback to make sure that notes are produced properly [4]. In one study, professional opera singers and vocal students showed increased activation in the bilateral vSI compared to laymen (medical students), but not in the auditory cortex [6].…”
Section: Introductionsupporting
confidence: 69%
“…For example, the vSI was activated bilaterally even in the simplest speech task, such as overt speaking of a single syllable [3]. Similar results were reported in singing, another sophisticated orofacial and laryngeal function in humans (for review see [4]): the vSI is activated bilaterally in a simple singing condition where subjects were asked to produce bisyllabic words melodically intoned at a certain pitch, and even during humming [5]. Moreover, several lines of evidence suggest that trained singers may rely more on somatosensory feedback than auditory feedback to make sure that notes are produced properly [4].…”
Section: Introductionsupporting
confidence: 66%
“…Geová Oliveira de Amorim (1) Lucas Carvalho Aragão Albuquerque (2) Leandro de Araujo Pernambuco (3) Patricia Maria Mendes Balata (4) Brunna Thaís Luckwü-Lucena (3) Hilton Justino da Silva (2) …”
Section: Contribuições Da Neuroimagem No Estudo Da Voz Cantada: Revisunclassified